Regional Transmission Network Modelling for Facilitating Congestion Management - KRSTEVSKI, Petar; Krkoleva Mateska, Aleksandra; Angelov, Jordanco; Borozan, Vesna; Taleski, Rubin (Wydawnictwo SIGMA-NOT, sp. z.o.o., 2015)
This paper provides convenient solutions for creation of transmission network models for power flow calculation for regional interconnected electric power systems. The creation of network models is based on data provided from different Transmission System Operators (TSOs) in standard data exchange format for this purpose. The automation of the model creating process facilitates the work of the TSOs in the field of congestion management and power system operational planning.
Keywords: Electric power system, Regional transmission network